Piezoelectric properties of PVDF‐conjugated polymer nanofibers. Issue 28 (4th March 2021) - Trevino, Julio E.; Mohan, Swati; Salinas, Alexandra E.; Cueva, Emilia; Lozano, Karen
Abstract: This study presents the development and characterization of PVDF‐conjugated polymer nanofiber‐based systems. Five different conducting polymers (CPs) were synthesized successfully and used to create the nanofiber systems. The CPs used are polyaniline (PANI), polypyrrole (PPY), polyindole (PIN), polyanthranilic acid (PANA), and polycarbazole (PCZ). Nanofiber systems were produced utilizing the Forcespinning® technique. The nanofiber systems were developed by mechanical stretching. No electrical field or post‐process poling was used in the nanofiber systems. The morphology, structure, electrochemical and piezoelectric performance was characterized. All of the nanofiber PVDF/CP systems displayed higher piezoelectric performance than the fine fiber PVDF systems. The PVDF/PPY nanofiber system displays the highest piezoelectric performance of 15.56 V. The piezoelectric performance of the PVDF/CP nanofiber systems favors potential for an attractive source of energy where highly flexible membranes could be used in power actuators, sensors and portable, and wireless devices to mention some. Abstract : This study focuses on the development of flexible, light‐weight fiber mats with promising potential to be used as sources of portable electrical energy. The developed fiber mats convert mechanical energy (compression) into electrical energy.